1996
DOI: 10.1021/jp9528525
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and Kinetics of Triplet 4-Methylbenzenesulfonylnitrene

Abstract: Triplet 4-methylbenzenesulfonylnitrene 3 was studied by solution phase laser flash photolysis, low-temperature absorption spectroscopy, and low-temperature EPR spectroscopy. Upon laser flash photolysis of 4-methylbenzenesulfonyl azide 1 in ethanol, absorption maxima were observed at 325 and 460 nm while in cyclohexane, a single maximum was observed at 310 nm. The short-wavelength absorptions were assigned to the triplet nitrene. There was no evidence that hydroxylic solvents catalyzed intersystem crossing from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 47 publications
3
29
1
Order By: Relevance
“…
Dedicated to Prof. Werner Uhl on the occasion of his 60th birthday Sulfonylazides, RSO 2 N 3 , are widely used diazo [1] and azide [2] transfer reagents, and in particular the photolytic or thermal elimination of N 2 from these azides have been well-studied. [3] Although the latter routes are generally used for the in situ generation of sulfonyl nitrenes, RSO 2 N, both were found to be complicated owing to secondary product formation, such as SO 2 + RN, as well as the pseudo Curtius rearrangement product RN = SO 2 . [3, 4] Recently it became apparent that initially formed reactive singlet sulfonyl nitrenes might be rapidly quenched by efficient intersystem crossing (ISC) to yield the lowerenergy triplet nitrenes of sluggish reactivity.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Dedicated to Prof. Werner Uhl on the occasion of his 60th birthday Sulfonylazides, RSO 2 N 3 , are widely used diazo [1] and azide [2] transfer reagents, and in particular the photolytic or thermal elimination of N 2 from these azides have been well-studied. [3] Although the latter routes are generally used for the in situ generation of sulfonyl nitrenes, RSO 2 N, both were found to be complicated owing to secondary product formation, such as SO 2 + RN, as well as the pseudo Curtius rearrangement product RN = SO 2 . [3, 4] Recently it became apparent that initially formed reactive singlet sulfonyl nitrenes might be rapidly quenched by efficient intersystem crossing (ISC) to yield the lowerenergy triplet nitrenes of sluggish reactivity.
…”
mentioning
confidence: 99%
“…[3] Although the latter routes are generally used for the in situ generation of sulfonyl nitrenes, RSO 2 N, both were found to be complicated owing to secondary product formation, such as SO 2 + RN, as well as the pseudo Curtius rearrangement product RN = SO 2 . [3, 4] Recently it became apparent that initially formed reactive singlet sulfonyl nitrenes might be rapidly quenched by efficient intersystem crossing (ISC) to yield the lowerenergy triplet nitrenes of sluggish reactivity. [4] Thermally persistent triplet FSO 2 N was produced by flash pyrolysis (ca.…”
mentioning
confidence: 99%
“…This analytical method (20)(21)(22)(25)(26)(27)(28) provides direct evidence for Rhnitrene formation and the ability of this two-electron oxidant to react through hydrogen atom abstraction. Previous studies using computational and spectroscopic methods estimate that the nitrenoid species has a half-life in the nanosecond to microsecond regime (29)(30)(31)(32), underscoring the impressive capabilities of DESI-MS to capture transient intermediates in solution-phase catalytic cycles of complex reactions. It should be recognized, however, that this mass spectrometric study identifies numerous transient species, but does not explicitly establish the kinetic competency of a particular species on the reaction coordinate.…”
mentioning
confidence: 99%
“…One such intermediate is the nitrene (represented below) and its chemistry generated from azide sources has been studied extensively in the last several decades. [6][7][8][9][10] N R…”
Section: Nitrenes and Their Photochemical Precursorsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Although most nitrenes have triplet ground states by substantial margins, aroyl nitrenes generated from aroyl azides have been notable in exhibiting primarily singlet reactivity. 7 For example, acyl nitrenes generated from the corresponding azide precursors have led to stereospecifically trapped products, indicative of singlet nitrene reactivity. 5,7 Theoretical calculations and matrix isolation studies on acyl nitrenes [5][6][7][8][9] have shown that the singlet state is lower in energy than the triplet state due to an interaction between the carbonyl oxygen and the hypovalent nitrogen.…”
Section: Introductionmentioning
confidence: 99%